If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3x = 5x + 7 Reorder the terms: 5 + 3x = 7 + 5x Solving 5 + 3x = 7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + 3x + -5x = 7 + 5x + -5x Combine like terms: 3x + -5x = -2x 5 + -2x = 7 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -2x = 7 + 0 5 + -2x = 7 Add '-5' to each side of the equation. 5 + -5 + -2x = 7 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 7 + -5 -2x = 7 + -5 Combine like terms: 7 + -5 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 60=4(6r+3) | | Z-4.3=1.6 | | x+(3x+11)=3 | | (11x-1)+(5y-5)=180 | | -12x+8y=-12 | | -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 | | 4=m/7+5 | | 5n=-3n | | v^3=37 | | 4(x-4)+8=12 | | 2(x+4)+3=15 | | 55=x-48 | | 3x-2=8x-1 | | 6.43-10d=2.5 | | -2c+5=-c+2 | | 9x+15=14x-11 |